Digitale Mathematikwerkzeuge als Mittler im bilingualen Mathematikunterricht im MISTI GTL Germany und an der GISB: Theoretische Rahmung aus Instrumentaler Genese und 4C Framework (mathematica didactica, 2021)
If digital media is used in bilingual learning environments, they can act as mediators and help to deal productively with culturally determined differences. Although mathematics is considered to be universal, it can be argued that there are differences in school mathematics in diverse countries. These differences are highly relevant for bilingual mathematics education and are important when using digital media. Two examples of American German bilingual teaching and learning environments are examined in this context; Mathematic lessons within the MISTI Global Teaching Lab program and at the German International School Boston. Against the background of the study results, the theory of instrumental genesis can be supplemented with regard to linguistic and cultural aspects of the 4C framework.